(untitled) (IAHS Medical Journal, 2022)
Background: Unscheduled uterine bleeding or abnormal uterine bleeding after menarche can occur due to ovulatory dysfunction between the age of 10 to 18 years. But the perception of the normal menstrual cycle makes worries to these girls and families because they have fear of the adverse effect of these on their future reproductive function. Evaluation of teen-aged girls can help us to exclude pathology and alleviate anxiety from her and their families. The aim of the study is to see the prevalence of unscheduled uterine bleeding in teen-aged girls attending OPD, in tertiary level hospitals. Materials and methods: A total of 100 cases were included in this study between June 2019-June 2020. Patients at post menarche period presenting with abnormal uterine bleeding or unscheduled uterine bleeding were included. Clinical diagnosis was made based on history, clinical examinations & investigations. Clinical diagnosis according to FIGO ovulatory dysfunctions was revealed in most of the cases.But in adults, according to PALM-COEIN most of the cases are due to organic causes was detected. Detailed discussion about the study was done with patient & parents. Informed consent was taken from them. Data was collected in a predesigned data collection sheet. Data were expressed in terms of percentage. Results: Most of the patients were in the age group of 8-14years (54%), 35% were between 14-18 years. 60% of the study patients were from urban areas. About 78% of parents had a monthly income of > 20,000 taka. Most of the patients were presented with heavy menstrual bleeding. 43% presented with bleeding for 7-10 days, 40% bleeding for > 10days & irregular continuous bleeding in 17% cases. Most of the patients needed more than an average numberof pads used per cycle. 15% needed double protections. Only 20% of the study patients had a regular cycle, but most of them (63%) had irregular cycles and in 17% of cases no cycle pattern was maintained. On examination for other associated features, 97% had normal secondary development according to Tanner’s stage, only 3% showed delayed development. In this study, BMI was normal in 30% cases, 58% were overweight, 10% were obese, 2% were morbidly obese. On clinical evaluation, pulse rates were within the normal range in 25% cases, 60% had tachycardia, 15% had pulse more than 110/min. Hypotension was recorded in 15% of cases. Regarding investigation findings, Hb% was < average in all cases, 33% had 8-10g%,65% had 7-8g% & < 7g% in about 12% cases. Hypothyroidism was detected in 6% of patients, & pelvic ultrasound was normal in all cases. Conclusions: Abnormal Uterine Bleeding – Ovulatory Dysfunction (AUB- O) was the leading cause of unscheduled uterine bleeding during post menarche period. IAHS Medical Journal Vol 4(1), June 2021; 5-8